Relationship between Physical Activity and Health-Related Physical Fitness in 16-Year-Old Boys (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. It is well established that regular physical activity (PA) has many short- and long-term beneﬁ ts for children’s health. Physically active children are more physically ﬁ t than their physically inactive counterparts. Insufﬁ cient physical ﬁ tness of adolescents is one of the risk factors for chronic diseases and has a tendency to be carried over into adulthood. Research aim was to examine health-related physical ﬁ tness in low, moderate and vigorous physical activity categories among 16-year-old schoolboys.Research methods. The participants were 155 healthy schoolboys of the 10 th  grade from secondary schools of Kaunas (Lithuania). Their physical activity was measured by a modiﬁ ed short form of the International PA Questionnaire (IPAQ) (Craig et al., 2003). The respondents were divided in three PA categories: high (vigorous) (VPA) (n = 43), moderate (MPA) (n = 63), and low (LPA) (n = 49). Physical ﬁ tness tests were performed to measure participants’ ﬂ exibility (by sit-and-reach test) (Euroﬁ t, 1993), power (by vertical jump test), and muscular strength and endurance (by modiﬁ ed push-up test) (Suni et al., 1994). Research results. There were no signiﬁ cant differences between the boys in different PA groups in respect of anthropometrical and body composition parameters (p > 0.05). The results of health-related physical ﬁ tness tests were signiﬁ cantly better of the VPA group boys (p < 0.05). The total volume of PA correlated with all health-related physical ﬁ tness components that were measured (r = 0.23–0.38, p < 0.01). Discusion and conclussions. We may conclude that health-related physical ﬁ tness is positively related to the total amount of physical activity in 16-year-old schoolboys.Keywords: frequency, duration, intensity, volume, physical activity, physical fitness.